Maturation period of bovine meat subjected to vacuum modifies physical-chemical and microbiological parameters (Revista de Ciências Agroveterinárias, 2018)
The objective of this research was to evaluate the effects of vacuum maturation on the changes of beef quality up to 9 days of refrigeration. The Longissimus dorsi muscle from 20 crossbred (Charolais x Angus) cattle was used in the research. The samples were distributed in three vacuum-ageing periods: T0 = zero (no vacuum), T3 = 3, T7 = 7 and T9 = 9 days, with five replicates for each period evaluated. During the ageing period, pH, color (L*, a*, b*), hue, chroma, water retention capacity, cooking loss and shear force were determined. The progress of vacuum-ageing changed (p
Keywords: ageing meat; Longissimus dorsi; meat tenderness and pH